The influence of financial literacy, financial attitude, and lifestyle on financial management behavior in paylater usage among generation Z: The moderating role of locus of control - Veneya, Keisha; Dehandri, Visca Aretha; Lidiyawati, Lidiyawati (Edelweiss Applied Science and Technology, 2025)
Using Locus of Control as a moderating variable, this study investigates the influence of financial literacy, financial attitudes, and lifestyle on financial management behavior among Generation Z Paylater users in Indonesia. A purposive sampling method collected 400 valid responses through an online survey using a 5-point Likert scale. Data were analyzed using SPSS version 26 with multiple linear regression. Results show that financial literacy, financial attitudes, and lifestyle significantly affect financial management behavior. However, the moderating role of Locus of Control varies. It does not influence the relationship between financial literacy and financial management behavior but weakens the association between financial management behavior and both lifestyle and financial attitudes. A strong internal Locus of Control may reduce the impact of lifestyle choices and attitudes. These findings highlight the importance of promoting financial literacy and responsible attitudes to improve financial behavior, particularly amid the growing use of Paylater services. Financial service providers and regulators are encouraged to strengthen financial education and apply stricter credit eligibility criteria to foster responsible borrowing among youth. Further research should include more behavioral variables and diverse demographic groups.